Omnibus Law dan Pengelolaan Ziswaf di Indonesia - Muhamad Wildan Fawaid (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2022)
The Ombibus Law (UU Cipta Kerja) was created to facilitate the flow of investment and a healthy entrepreneurial climate in Indonesia, by cutting various kinds of bureaucratic rules that overlap and are mutually counterproductive. The Job Creation Law only focuses on employment and investment and does not clearly emphasize the position of Ziswaf which should be used as other income apart from taxes. The actual Ziswaf potential is far greater than the tax itself. This study uses a descriptive analysis method, with common law legal theory which is trying to be applied in civil law countries. Indonesia should be able to learn from the countries of Malaysia and Singapore which have succeeded in making Ziswaf as another source of income apart from taxes. Even though their country is common law and the population is much less than Indonesia. The government is still looking at the use of cash waqf for investment rather than thinking about uniting all the strengths of LAZ in the Baznas body and managing it professionally. It is not impossible that with such management, Indonesia will achieve its target of 233 trillion zakat potential.